Fungal community dynamics across a forest–alpine ecotone. Issue 19 (10th August 2021) - Tonjer, Lea‐Rebekka; Thoen, Ella; Morgado, Luis; Botnen, Synnøve; Mundra, Sunil; Nybakken, Line; Bryn, Anders; Kauserud, Håvard
Abstract: Climate change is causing upward shift of forest lines worldwide, with consequences for soil biota and carbon (C) sequestration. We here analyse compositional changes in the soil biota across the forest line ecotone, an important transition zone between different ecosystems. We collected soil samples along transects stretching from subalpine mountain birch forests to alpine heath. Soil fungi and micro‐eukaryotes were surveyed using DNA metabarcoding of the ITS2 and 18S markers, while ergosterol was used to quantify fungal biomass. We observed a strong shift in the soil biota across the forest line ecotone: Below the forest line, there were higher proportions of basidiomycetes and mucoromycetes, including ectomycorrhizal and saprotrophic fungi. Above it, we observed relatively more root‐associated ascomycetes, including Archaeorhizomycetes, ericoid mycorrhizal fungi and dark septate endophytes. Ergosterol and percentage C content in soil correlated strongly and positively with the abundance of root‐associated ascomycetes. The predominance of ectomycorrhizal and saprotrophic fungi below the forest line probably promote high C turnover, while root‐associated ascomycetes above the forest line may enhance C sequestration. With further rise in forest lines, there will be a corresponding shift in the below‐ground biota, probably leading to enhanced release of soil C.